Exploration and evaluation of the mathematical values inculcation instrument - Liman, Mukhtar Alhaji; Ibrahim, Mohd Burhan; Isma'il, Yusuf (Academic Journals, 2013)
The concept of a values system in education including mathematics education cannot be over emphasized. This is because value based education stands to be the rudiment of classical successes in the attainment of beneficial knowledge, that is the knowledge which is cognizant of the material and spiritual needs of the individual and the society. This study aims at investigating and understanding the underlying factors of values inculcation in mathematics teaching and learning among mathematics teachers in the North eastern region of Nigeria. As such, this paper xplores some of the universal values that are supposed to be tele-guiding mathematics instructional content delivery. The study involved n=509 service teachers teaching mathematics at various levels of secondary school education in the North eastern region of Nigeria. A likert-scale questionnaire consisting of 52 items cutting across the five hypothesized dimensions of values inculcation in athematics teaching and learning which include ideological, attitudinal, sociological, computational and motivational mathematical values was used to obtain the teachers’ responses on the nature of the values they inculcate in their mathematics teaching and learning. The study intends to answer the research questions and hypotheses based on the predictive abilities of mathematical values inculcation measures and mathematical values inculcation measures that effectively predict the underlying five constructs for values inculcation. The results show that out of the 52 items proposed to measure the five latent constructs only 43 items clinched to the hypothesized five dimensions. This implied that values inculcation in mathematics teaching and learning should be geared using the five factor dimensions analysed in this study, particularly in the North eastern region of Nigeria.